Effects of sucrose, sugar alcohols and whey protein concentration on foaming properties of native whey protein concentrate and whey protein isolate - Bong, Davin (My University, 2010)
Whey proteins are utilized in the food industry as foaming agents and consequently whey protein foams are an integral component of many foods such as meringue and whipped cream. The aim of the study was to investigate the effects of carbohydrates (sucrose, maltitol and sorbitol) on the foaming properties of native whey proteins (Native WPC-80). Additions of sucrose, maltitol and sorbitol (10% (2/2)) to a solution containing 5% native whey proteins resulted in significantly (P<0.05) lowered foam overrun. In contrast, the foam stability of native whey proteins was significantly enhanced when sucrose, maltitol and sorbitol were separately incorporated into 5% native WPC-80 solution. An increase in solution viscosity due to carbohydrate addition was disadvantageous for air incorporation but significantly increased the strength of foam lamella wall surrounding foam air bubbles. The net effect of this increase in solution viscosity was poorer foaming ability but better foam stability of native whey proteins. The effect of various whey protein concentrations was evaluated at 2%, 5% and 8% using two commercial WPI and native WPC-80. An increase in whey protein concentration increased both foam overrun and foam stability. This could be attributed to increased concentration of proteins that were absorbed into air-water interface of the foam system and thicker, more rigid interfacial lamellar films which in turn retarded serum drainage.
Effects of sucrose, sugar alcohols and whey protein concentration on the foaming properties of native whey protein concentrate and whey protein isolate
29 p.
Keywords: Food Science